Evaluation of hormonal and circulating inflammatory biomarker profiles in the year following bariatric surgery - Kim, Eun Ran; Yun, Ji Ho; Kim, Hyo-Jin; Park, Hyeon Young; Heo, Yoonseok; Park, Young Suk; Park, Do Joong; Koo, Soo Kyung (Frontiers in Endocrinology, 2023)
Background: Bariatric surgery (BS) has a superior effect on reducing body weight and fat in patients with morbid obesity. As a result, BS mitigates obesity-related complications such as type 2 diabetes (T2D). However, few studies have shown the mechanism underlying diabetes remission after surgery. This study aimed to investigate the differences in serum hormone and inflammatory cytokine levels related to diabetes before surgery and during 12 months of follow-up in obese Korean patients with obesity. Methods: The study participants were patients with morbid obesity (n=63) who underwent sleeve gastrectomy (SG) or Roux-en-Y gastric bypass (RYGB) between 2016 – 2017 at seven tertiary hospitals in Korea. The patients were followed for 1 year after surgery. Results: Sixty-three patients had significant weight loss after surgery and showed improvements in clinical parameters and hormonal and inflammatory profiles. Among them, 23 patients who were diabetic preoperatively showed different remission after surgery. The levels of inflammation-related clinical parameters changed significantly in the remission group, and serum inflammatory cytokine and hormones significantly decreased at certain points and showed an overall decreasing trend. Conclusions: Our study found postoperative changes of factors in blood samples, and the changes in hormones secreted from the three major metabolic tissue (pancreas, adipose, and gut) along with the differences in multi-origin inflammatory cytokines between remission and non-remission groups provide a path for understanding how the effect of BS in improving glucose metabolism is mediated.